The students' perceptions about their field at school of vocational sciences - Kahvecioğlu, Habibe; Yıldırım, Osman (Int Scientific Conference SGEM, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
As it is well-known, students' vocational choice and students' personally types are very important regarding of the effectiveness of academic programs. This research aims at clarifying the relation between students' personality types and their choices by using students' perceptions. The research has been conducted on 352 students attending at School of Vocational Studies. According to the research findings, there are strong relationships between students' personality types and their choices. Based on The Five Factor Model, Inventory is an evaluation tool which is improved according to the Turkish culture. Validity and reliability analysis (dimensional self consistency cofactors vary between 0,71 and 0,88; test repeat cofactors vary between 0,83 and 0,91) show that inventory consists strong psychometric features. The results obtained from inventory were evaluated by using raw points and not norm points. In the short version of the Inventory only the five dimensions (openness for experience, responsibility consciousness, being extrovert, compatibleness, emotional balance) of the character are evaluated using total 25 attributes. The answers for the attitudes are classified in Likert scale 5. If the answers are totally suitable the grade given is 5, if totally not suitable the grade given is 1.
Keywords: Students' Perceptions; Five Factor Model; Students'Choices; Personality Types; Training Effectiveness